2019
DOI: 10.1002/asl.941
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic study of extreme precipitation over Kerala during August 2018

Abstract: The state of Kerala, located on the west coast of India, experienced a record 100‐year flood that resulted in major landslides from unprecedented prolonged and extremely heavy rainfall (50–480 mm·day−1) during August 1–19, 2018, causing extensive damage and about 500 causalities. Rainfall observations indicate that the heavy rainfall occurred over two spells (August 7–10 and 14–18) in association with an offshore trough, and a depression over the Bay of Bengal (BOB). High‐resolution 38‐year climatology data (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…Of late, several heavy rainfall events have been reported in these states (e.g. Srinivas et al ., 2018; Viswanadhapalli et al ., 2019). Interestingly, one common factor across these states is an apparent urbanization as implied by the increasing industrial activity and migration to cities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of late, several heavy rainfall events have been reported in these states (e.g. Srinivas et al ., 2018; Viswanadhapalli et al ., 2019). Interestingly, one common factor across these states is an apparent urbanization as implied by the increasing industrial activity and migration to cities.…”
Section: Discussionmentioning
confidence: 99%
“…The Weather Research and Forecasting (WRF) model version 3.8.1 (Skamarock et al ., 2008), which is a mesoscale numerical weather prediction system designed for atmospheric research and operational forecasting needs, is employed in this study. The WRF model predictability of heavy rainfall events over the Indian region has been ascertained in several studies (Sahany et al ., 2010; Hariprasad et al ., 2011; Bhanu Kumar et al ., 2012; Chawla et al ., 2018; Srinivas et al ., 2018; Viswanadhapalli et al ., 2019). For this study, the model has been configured with three two‐way interactive nested domains with horizontal outer‐to‐inner resolutions of 18, 6 and 2 km.…”
Section: Datasets and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Viswanadhapalli et al. (2019), Baisya and Pattnaik (2019), and Chakraborty et al. (2021) simulated the Kerala heavy rainfall event during 2018 and identified strong westerly jet, the transport of mid‐tropospheric moisture, and the horizontal moisture flux convergence as the critical drivers of convection.…”
Section: Introductionmentioning
confidence: 99%
“…The extreme precipitation and runoff conditions observations made by Mishra et al using the Variable Infiltration Capacity (VIC) model, have shown that the 2018 extreme flood event was unprecedented in the last seven decades from 1951-2018 [33]. The simulation results by Viswanadhapalli et al, suggested that the high convective instability and transport of mid-tropospheric moisture from the Bay of Bengal were the driving factors behind the heavy rainfall over Kerala in 2018 [34]. The change in water levels of reservoir storage during extreme rainfall of Kerala in 2018 were also discussed by Ramasamy et al, Anandalekshmi et al,.…”
Section: Introductionmentioning
confidence: 99%